2020
DOI: 10.1016/j.pmedr.2020.101229
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of breast cancer risk self-assessment does not correlate with knowledge about breast cancer and knowledge and attitudes towards primary chemoprevention

Abstract: Highlights 72% of high-risk women underestimate their own breast cancer risk. Positive family history does not encourage positive chemoprevention attitude. Low general knowledge about breast cancer chemoprevention detected. High interest in chemoprevention gives an opportunity for its implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…In addition, our results are higher than those from a recent study by Seven et al (2018) in Turkey, where only about 20% of women with a history of BC ranked their risk as low, while 51.3% ranked their risk as moderate where numeric measure of risk perception was used 20 . Women with high risk to BC including women with family history of BC have often underestimated their own risks to BC 21 . Sometimes low risk perception to a disease to which one is susceptible could be a self‐defence mechanism to deal with the reality and perceived danger of the disease.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In addition, our results are higher than those from a recent study by Seven et al (2018) in Turkey, where only about 20% of women with a history of BC ranked their risk as low, while 51.3% ranked their risk as moderate where numeric measure of risk perception was used 20 . Women with high risk to BC including women with family history of BC have often underestimated their own risks to BC 21 . Sometimes low risk perception to a disease to which one is susceptible could be a self‐defence mechanism to deal with the reality and perceived danger of the disease.…”
Section: Discussioncontrasting
confidence: 89%
“…20 Women with high risk to BC including women with family history of BC have often underestimated their own risks to BC. 21 In this study, we found that BC perceived risk was significantly associated with the age of the participant. Women aged 36-46 years were more likely to perceive themselves to be at high risk of developing BC compared to those aged 18-25 years.…”
Section: Discussionmentioning
confidence: 55%
“…Disagreements were resolved through discussion with a third researcher (ANA) to reach consensus. 4 articles were removed as two articles focused on accuracy of risk perception on breast cancer [ 22 , 23 ] and another two articles described the validation of questionnaire assessing awareness but not perception of breast cancer [ 24 , 25 ], leaving a total of 86 articles to proceed with quality appraisal.…”
Section: Methodsmentioning
confidence: 99%